Numerical study of heat transfer enhancement using vortex generator for thermal management of lithium ion battery. (February 2019) - Xie, Junling; Xie, Yuanyuan; Yuan, Chris
Highlights: Air flow model coupled with a lithium-ion pouch-cell model is created for the study. Two types of vortex structure have been evaluated for the enhanced battery cooling. The maximum temperature of a pouch cell at 5c rate can be decreased by 10%. The local Nusselt number at 5c rate can be increased by 38%. Abstract: A numerical study of two types of vortex generator (VG) have been conducted to enhance heat transfer of cooling in the battery thermal management system. The thermal behaviour and cooling effects have been investigated to evaluate the heat transfer performance of two types of VG. Air flow model coupled with a pouch cell model is carried out in this study. The results show that both types of vortex generators can enhance heat transfer before VGs, but only delta winglet VG can still enhance local heat transfer after it due to more vortices generated that can mix cold and hot air flow between the top and bottom thermal layers completely. It is found that the heat transfer enhancement is due to bulk fluid mixing, boundary-layer modification and flow destabilization by VGs. The maximum temperature of pouch cell is also numerically investigated by a validated battery model. The result shows that the maximum temperature of a pouch cell can be decreased by both delta winglet and rectangular rib. For the discharging rate at 5C, it can be decreased by 10% and the local Nusselt number can be increased by 38% compared to the baseline scenario without any VGs.